Efektivitas Mesin Filling Tabung Gas 3 Kg Menggunakan Metode Overall Equipment Effectiveness (OEE) di PT. XYZ - Latjengke, Mohamad Julfikar; Lahay, Idham Halid; Simatupang, Rudolf (LPPM Universitas Pahlawan Tuanku Tambusai, 2025)
At PT Putra Argam Mandiri there are still product defects in every distribution process. Product defects that are often found at PT Argam are hang guards and foot rings that are peyot due to being crushed with other products during transportation and leaking bodies. The number of defective products produced on average for the last 6 months period reached 487 units. So that the Overall Equipment. Effectiveness method is needed in order to streamline the performance of the tool and be able to function as it should. That way the tool will work properly and will produce quality productsBased on the research conducted, the conclusions obtained from the results of the OEE calculation on the Filling machine PT. Putra Argam Mandiri during the period October 2024 to March 2025 resulted in an average OEE of around 86.55%.